Design of reconfigurable circularly polarised double folded inverted‐L antenna with rectangular ground plane using HFSS. Issue 5 (22nd September 2020) - Praveen Kumar, Padakandla Chenna; Trinatha Rao, Polipalli
Abstract : A novel design of reconfigurable circularly polarised antenna is proposed and developed in the present work. The circularly polarised antenna consists of two linearly polarised inverted‐L antenna elements with double‐folded arms. To improve the impedance matching and radiation characteristics, the double‐folded structure plays a significant role. Circular polarisation is achieved by properly adjusting the lengths of two arms, quadrature currents can be produced on two orthogonal elements. The developed linearly polarised antenna elements are low‐profile and small in size, the circularly polarised antenna structure is minimised to be about 70 mm in length, 70 mm width and 18 mm in height (70 × 70 × 18 mm). The feeding configuration is simplified by using coaxial probe instead of an external polariser, better values are obtained between the theoretical calculations and simulated results, which validate the design concept. The designed reconfigurable circularly polarised double folded inverted‐L antenna is compared with twin inverted‐L shaped structure. The simulated results show that the circularly polarised antenna resonates at 2.39 GHz and has a wide impedance bandwidth of 6.00% S 11 with −32.16 dB and VSWR<2 and 3 dB axial ratio of 1.2 across the entire operating band.